Telecommunications is Dead, Long Live Networking : The Effect of the Information Revolution on the Telecom Industry - Bond, James (World Bank, Washington, DC, 2012)
The author looks at how the drivers of the information revolution are transforming the structure of the telecommunications industry. The end of natural monopoly, the breakdown of the old pricing mechanisms, the increasing competition from new operators and new products, and the globalization of the industry are forcing radical change. This spells trouble for incumbent telecommunications operators -most of whose assets are holes in the ground. Many incumbents are responding by forming global alliances. But this trend may have more to do with their desire to recreate in international markets the oligarchies they are used to at home than with the underlying market forces. Where is the industry heading? One view of the future sees transmission capacity and bandwidth becoming tradable commodities, with the industry fragmenting into wholesalers investing in capacity, brokers intermediating supply and demand for capacity, and retailers dealing with the consumer.